Fish Trapping Devices and Methods of Southern India - K.V., Mohan Rajan (Fishery Technology, 2025)
Traps are impounding devices into which an organism is lured and from which escape is made difficult. Trap fisheries have economic and energy related advantage over active search and capture fisheries. A review of I5 types of impounding devices and methods which were prevalent in the immediate past or are still in use in southern India is presented in this paper, broadly following the classification for fishing gear categories as recom- mended by FAO.